Dyeing Studies with Eucalyptus, Quercetin, Rutin, and Tannin: A Research on Effect of Ferrous Sulfate Mordant. (30th April 2013) - Mongkholrattanasit, Rattanaphol; Klaichoi, Charoon; Rungruangkitkrai, Nattadon; Punrattanasin, Nattaya; Sriharuksa, Kamolkan; Nakpathom, Monthon
Abstract : Natural dyes from Eucalyptus leaf extract, quercetin, rutin, and tannin were applied to silk fabric by pad-batch and pad-dry techniques under different conditions. Ferrous sulfate was used as a mordant. The dyeing properties were evaluated by measuring K/S and CIELAB values. In addition, the different fastness properties were evaluated. The effect of dyes at different concentration levels with respect to their colour strength was also studied.